On the question of relations between the state and evangelical Christians-Baptists (on the example of the Saratov Volga region) - Yakovlevа, Jeanne Vladimirovna (Известия Саратовского университета. Новая серия. Серия: История. Международные отношения, 2025)
The article is devoted to the analysis of the relationship between the state and Evangelical Christians-Baptists throughout the history of their existence in the Saratov Volga region. These relationships have gone through a complex and contradictory path from their rejection by the Russian Orthodox Church and the state to the inclusion of the religious community in the social life of society. The ideas and activities of the community at the present stage of history have become entrenched in society and have become the norm as a result of a gradual shift in the window of discourse. As a result of this process, over time, Evangelical Christians-Baptists have had the opportunity to express and defend ideas that were previously considered radical or unacceptable.